2017
DOI: 10.1261/rna.057877.116
|View full text |Cite
|
Sign up to set email alerts
|

The structure of an E. coli tRNAfMet A1–U72 variant shows an unusual conformation of the A1–U72 base pair

Abstract: Translation initiation in eukaryotes and archaea involves a methionylated initiator tRNA delivered to the ribosome in a ternary complex with e/aIF2 and GTP. Eukaryotic and archaeal initiator tRNAs contain a highly conserved A-U base pair at the top of the acceptor stem. The importance of this base pair to discriminate initiator tRNAs from elongator tRNAs has been established previously using genetics and biochemistry. However, no structural data illustrating how the A-U base pair participates in the accurate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have shown that E. coli initiator Met-tRNA f Met A 1 -U 72 variant was a good mimic of Pa-Met-tRNA i Met with identical acceptor stem and anticodon loop ( Supplementary Figure S5 , ( 24 , 30 , 40 )). Therefore, because Met-tRNA f Met A 1 -U 72 tRNA can be obtained with a much higher purity than Pa-Met-tRNA i Met ( 40 ), toeprinting experiments were performed with E. coli initiator Met-tRNA f Met A 1 -U 72 . Control experiments showed very similar toeprint signals with Met-tRNA f Met A 1 -U 72 as compared to Pa-Met-tRNA i Met ( Supplementary Figure S5B ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that E. coli initiator Met-tRNA f Met A 1 -U 72 variant was a good mimic of Pa-Met-tRNA i Met with identical acceptor stem and anticodon loop ( Supplementary Figure S5 , ( 24 , 30 , 40 )). Therefore, because Met-tRNA f Met A 1 -U 72 tRNA can be obtained with a much higher purity than Pa-Met-tRNA i Met ( 40 ), toeprinting experiments were performed with E. coli initiator Met-tRNA f Met A 1 -U 72 . Control experiments showed very similar toeprint signals with Met-tRNA f Met A 1 -U 72 as compared to Pa-Met-tRNA i Met ( Supplementary Figure S5B ).…”
Section: Resultsmentioning
confidence: 94%
“…tRNA f Met A 1 -U 72 was produced in PalΔmetZWVΔmetY::kan E. coli strain from PBSTNAV-tRNA f Met A 1 -U 72 , purified and aminoacylated as described ( 39 , 40 ). tRNA i Met , tRNA m Met and tRNA m Met 3G3C were produced in JM101Tr from cloned versions of the tRNAs ( 30 , 41 ), purified and aminoacylated as described ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…The electron density for the three terminal lysine residues of uS13 is missing. Interestingly, the guanidinium group of uS13-R145 occupies a position corresponding to that of A37 in its "unstacked" conformation observed in the anticodon loop of free initiator tRNA 13,52 . One may imagine that during tRNA accommodation, R145-uS13 selects G30-C40 in the 3 G-C pairs major groove and facilitates the motion of A37 towards the anticodon loop where it is stacked against U36 and A38.…”
Section: Resultsmentioning
confidence: 99%
“…The strategy used to prepare the IC2 complex was adapted from a previously described one 12 . In brief, archaeal 30S subunits from P. abyssi (Pa-30S) were purified and mixed with IFs Pa-aIF1A, the ternary complex Pa-aIF2:GDPNP:Met-tRNA i Met A 1 -U 72 and a synthetic 26 nucleotide-long mRNA corresponding to the natural start region of the mRNA encoding the elongation factor aEF1A from P. abyssi (A(−17)UUUGGAGGU-GAUUUAAA(+1)UGCCAAAG(+9)) 13 . The complex was purified by affinity chromatography (TALON, Clontech) using N-terminally tagged versions of Pa-aIF2β and Pa-aIF2α.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation